2016 European Society of Hypertension guidelines for the management of high blood pressure in children and adolescents. Issue 10 (October 2016) - Lurbe, Empar; Agabiti-Rosei, Enrico; Cruickshank, J. Kennedy; Dominiczak, Anna; Erdine, Serap; Hirth, Asle; Invitti, Cecilia; Litwin, Mieczyslaw; Mancia, Giuseppe; Pall, Denes; Rascher, Wolfgang; Redon, Josep; et al.
Abstract : Increasing prevalence of hypertension (HTN) in children and adolescents has become a significant public health issue driving a considerable amount of research. Aspects discussed in this document include advances in the definition of HTN in 16 year or older, clinical significance of isolated systolic HTN in youth, the importance of out of office and central blood pressure measurement, new risk factors for HTN, methods to assess vascular phenotypes, clustering of cardiovascular risk factors and treatment strategies among others. The recommendations of the present document synthesize a considerable amount of scientific data and clinical experience and represent the best clinical wisdom upon which physicians, nurses and families should base their decisions. In addition, as they call attention to the burden of HTN in children and adolescents, and its contribution to the current epidemic of cardiovascular disease, these guidelines should encourage public policy makers to develop a global effort to improve identification and treatment of high blood pressure among children and adolescents.